Palavras para avaliação fonológica da língua italiana: validação de conteúdo - d' Apolito, Aurora (2017)
The phonological assessment should fundamentally capture the phonological knowledge of the child with respect to segments, specifically regarding the internal structure of the segments and syllabic constituents of their mother tongue. In order to obtain a significant sample of the child's phonological system, it is essential to have a list of words that represents all the phonemes of the language in analysis, considering simple and complex onset. This study aimed to propose a list of validated words to compose a possible phonological assessment tool for the Italian language. The researcher has identified 2489 words based on children’s speech assessments in the Italian language. The words were classified by considering segments and their position on the syllable and the word. This list was evaluated by a group of subject matter experts (Italian speech- language pathologists) using PAROLE software. For each word, three choices were offered, from which, one single choice could be made. Then, through other statistical software, the content validity ratio (CVR) index was calculated for each item evaluated. Of the 2489 items, 131 words were considered valid to evaluate the phonemes in simple and complex onset position in Italian monolingual children between three years and eight years and 11 months. Among the selected words, it is observed that some are repeated to evaluate different phonemes. This must be evaluated in order to create a list of words with at least three occurrences of each segment in the different positions of the syllable and the word, being these pictorially representable to facilitate the elicitation of the words, and so that it is tested by other subject matter experts (children). The list of validated words, allowed the researchers to obtain an adequate number of stimuli to be used in a new phonological assessment tool for Italian monolingual children.